Formulation development of fast releasing oral thin films of levocetrizine dihydrochloride with EudragitÂ® Epo and optimization through Taguchi orthogonal experimental design - Lakshmi, P K; Sreekanth, J; Sridharan, Aishwarya (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of this study was to develop a fast releasing oral polymeric film, prepared using the solvent casting method, with good mechanical properties, instant disintegration and dissolution, an acceptable taste in the oral cavity. Levocetirizine dihydrochloride, an antihistamine, was incorporated to relieve the symptoms of allergic rhinitis. Four batches of films with drug were prepared using different combinations of polymers and plasticizers EudragitÂ® EPO, HPMC E 5 LV, and PVA were the selected polymers. Glycerin, dibutyl phthalate, propylene glycol, and PEG 400 were the selected plasticizers.The resultant films were evaluated for weight variation, assay, content uniformity, folding endurance, thickness, tensile strength, percent elongation, surface pH, in vitro disintegration and in vitro dissolution.The formulations from the preliminary trial were analyzed using Taguchi OA experimental design, which was applied to optimize the type of polymers, concentration of polymers, plasticizer, and sweetener based on their disintegration data at three different levels.The optimized films disintegrated in less than 30s, releasing 70-90% of drug within 2 mins.The percentage release varied with the type of polymer and concentration of polymer. The films made with EPO released 96% of drug in 2 mins, which was the best release among all.